Systemic Treatment of Metastatic Conjunctival Melanoma. - Torres, S (2017)
Conjunctival melanoma (CM) is an exceptionally rare tumor, with a propensity for local and distant recurrence, with the lungs, skin, liver, and brain being the most common sites of metastasis. Recent progress in systemic treatments, with checkpoint inhibitors and targeted therapies blocking BRAF and MEK, has redefined the standard of care of advanced unresectable and metastatic melanoma. Although most trials did not include patients with conjunctival melanoma, its close molecular and genetic relationship to cutaneous melanoma might suggest a similar response to these novel agents. The authors describe two uncommon cases of metastatic conjunctival melanomas with distinct genetic profiles and, as such, submitted to different systemic treatments.